Intellectual giftedness for leadership: How robust is the crime reducing effect of intellectual class? - Burhan, Nik Ahmad Sufian; Che Razak, Razli; Selamat, Muhamad Rosli; Rosli, Muhamad Ridhwan (2017)
This paper aims to reassess Burhan et al.‟s (2014, Intelligence, 47, 12–22) findings on the impact of intelligence (IQ) on the crime rates at a cross-country level. People who belong to the intellectual group, characterized by IQ at the 95th percentile of a normal distribution were found to have a tremendous impact in terms of crime rate reduction, compared to those with average ability (50th percentile IQ). This was proven using the ordinary least squares (OLS). Other than that, people of non-intellectual class (5th percentile IQ) were found to be least important in reducing crime. However, in their study, many independent variables were stated as not significantly related to the crime rates, which contradicts with other literature. It is questionable if the presence of serious outliers in the samples causes the objectionable finding. In this study, we analyzed the impact of IQ classes on the rate of eight different types of crimes, namely homicide, rape, kidnapping, robbery, assault, burglary, property crimes, and vehicle theft. Analysis was carried out using the Tukey‟s Bisquare robust M-estimator that mitigates the effects of outliers in the samples. In conclusion, we have proved that those from the intellectual class have more significant role than people of average ability and non-intellectual class in reducing the crime rates. Thus, educational policies for the gifted are recommended in order for them to become active participants of the future transformation of their societies, by enhancing functionality and quality of the institutions across nations, and thereby, reducing crimes.